The prevention and management of chronic disease in primary care: recommendations from a knowledge translation meeting. (December 2015) - Ahmed, Sara; Ware, Patrick; Visca, Regina; Bareil, Celine; Chouinard, Maud-Christine; Desforges, Johanne; Finlayson, Roderick; Fortin, Martin; Gauthier, Josée; Grimard, Dominique; Guay, Maryse; Hudon, Catherine; et al.
Abstract Background Seven chronic disease prevention and management programs were implemented across Quebec with funding support from a provincial-private industry funding initiative. Given the complexity of implementing integrated primary care chronic disease management programs, a knowledge transfer meeting was held to share experiences across programs and synthesize common challenges and success factors for implementation. Methods The knowledge translation meeting was held in February 2014 in Montreal, Canada. Seventy-five participants consisting of 15 clinicians, 14 researchers, 31 knowledge users, and 15 representatives from the funding agencies were broken up into groups of 10 or 11 and conducted a strengths, weaknesses, opportunities, and threats analysis on either the implementation or the evaluation of these chronic disease management programs. Results were reported back to the larger group during a plenary and recorded. Audiotapes were transcribed and summarized using pragmatic thematic analysis. Results and discussion Strengths to leverage for the implementation of the seven programs include: (1) synergy between clinical and research teams; (2) stakeholders working together; (3) motivation of clinicians; and (4) the fact that the programs are evidence-based. Weaknesses to address include: (1) insufficient resources; (2) organizational change within the clinical sites; (3) lack of referrals from primary care physicians; and (4) lack of access to programs. Strengths to leverage for the evaluation of these programs include: (1) engagement of stakeholders and (2) sharing of knowledge between clinical sites. Weaknesses to address include: (1) lack of referrals; (2) difficulties with data collection; and (3) difficulties in identifying indicators and control groups. Opportunities for both themes include: (1) fostering new and existing partnerships and stakeholder relations; (2) seizing funding opportunities; (3) knowledge transfer; (4) supporting the transformation of professional roles; (5) expand the use of health information technology; and (6) conduct cost evaluations. Fifteen recommendations related to mobilisation of primary care physicians, support for the transformation of professional roles, and strategies aimed at facilitating the implementation and evaluation of chronic disease management programs were formulated based on the discussions at this knowledge translation event. Conclusion The results from this knowledge translation day will help inform the sustainability of these seven chronic disease management programs in Quebec and the implementation and evaluation of similar programs elsewhere.